2017
DOI: 10.1016/j.chom.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Bacterial Fermentation Products Increase Tuberculosis Risk in Antiretroviral-Drug-Treated HIV Patients

Abstract: Despite the immune-reconstitution with antiretroviral therapy (ART), HIV-infected individuals remain highly susceptible to tuberculosis (TB) and have an enrichment of oral anaerobes in the lung. Products of bacterial anaerobic metabolism, like butyrate and other short chain fatty acids (SCFAs), induce regulatory T cells (Tregs). We tested if SCFAs contribute to poor TB control in a longitudinal cohort of ART treated HIV-infected South Africans. Increase in serum SCFAs was associated with increased TB susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 50 publications
5
114
0
1
Order By: Relevance
“…Assessment of microbiota in BAL from TB patients revealed specific differences, with Cupriavidus as dominant genus, in lower respiratory tracts . The microbiome of individuals with detectable proprionate levels in BAL had a relative abundance of anaerobic bacteria , which is in line with the hypothesis that SCFA are produced locally in the lung. Together, these data indicate that the microbiome locally in the airways is disturbed during active TB disease; however, the differences in study populations (adults vs children, different ethnic origins including differences in diet), clinical samples (nasopharynx, sputum, BAL) and analysis methods make it impossible to draw any major conclusions on the alterations in microbiota composition during TB disease.…”
Section: The Role Of the Host Microbiome In Modulating Protective Tb supporting
confidence: 74%
See 1 more Smart Citation
“…Assessment of microbiota in BAL from TB patients revealed specific differences, with Cupriavidus as dominant genus, in lower respiratory tracts . The microbiome of individuals with detectable proprionate levels in BAL had a relative abundance of anaerobic bacteria , which is in line with the hypothesis that SCFA are produced locally in the lung. Together, these data indicate that the microbiome locally in the airways is disturbed during active TB disease; however, the differences in study populations (adults vs children, different ethnic origins including differences in diet), clinical samples (nasopharynx, sputum, BAL) and analysis methods make it impossible to draw any major conclusions on the alterations in microbiota composition during TB disease.…”
Section: The Role Of the Host Microbiome In Modulating Protective Tb supporting
confidence: 74%
“…In contrast, controls had more beneficial, commensal organisms of the Bacteroidetes phylum [194]. Furthermore, increased serum concentrations of SCFA, the products of the commensal bacteria, were associated with increased TB susceptibility in HIVinfected individuals [191]. Butyrate inhibited IFN-c and IL-17 production in response to Mtb-antigen stimulation of PBMCs [191], in a HDAC-dependent manner [195].…”
Section: Microbiome and Tbmentioning
confidence: 99%
“…Two recent studies have shown that the short chain fatty acid (SCFA) butyrate modulates the production of M. tuberculosis-induced pro-and anti-inflammatory cytokines in the lungs, associated with an increased susceptibility to M. tuberculosis (Lachmandas et al, 2016;Segal et al, 2017). Two recent studies have shown that the short chain fatty acid (SCFA) butyrate modulates the production of M. tuberculosis-induced pro-and anti-inflammatory cytokines in the lungs, associated with an increased susceptibility to M. tuberculosis (Lachmandas et al, 2016;Segal et al, 2017).…”
Section: How the Gut Microbiota Influences Anti-tb Immunity In The Lungsmentioning
confidence: 99%
“…Previous investigation showed systemic inflammation may be due to alterations in gut commensal microorganisms by a high-fat, high-caloric, low-fibre diet; this led to a high Firmicutes to Bacteroidetes (F/B) ratio in the gut microbiota, with further degradation of the gut epithelial barrier and leakage of lipopolysaccharide-positive (LPS+) bacteria. 3 To date, most studies on TB have focused on the interaction between respiratory microbiota and clinical outcomes, 4 whereas only a few have described the interaction between the host and microbiome with regard to short-chain fatty acids (SCFAs) and Treg activation. 4 Patients with active TB sometimes had concurrently increasedin both pro-and anti-inflammatory cytokines, such as IL-6, TNF, IFN-γ and IL-10, and leucocytosis in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…3 To date, most studies on TB have focused on the interaction between respiratory microbiota and clinical outcomes, 4 whereas only a few have described the interaction between the host and microbiome with regard to short-chain fatty acids (SCFAs) and Treg activation. 4 Patients with active TB sometimes had concurrently increasedin both pro-and anti-inflammatory cytokines, such as IL-6, TNF, IFN-γ and IL-10, and leucocytosis in peripheral blood. Some investigations showed that the Bifidobacteriaceae family may downregulate the inflammatory response after MTB infection, resulting in fewer constitutional symptoms.…”
Section: Introductionmentioning
confidence: 99%